Binder composition for lithium ion battery electrode
By using a specific proportion of poly(meth)acrylamide monomer and an unsaturated carboxylic acid-based monomer as the binder composition, the adhesive combination for lithium ion battery electrodes is solved by using a specific proportion of poly(meth)acrylamide copolymer with an unsaturated carboxylic acid-based monomer as the binder composition, the bonding agent combination for lithium ion battery electrodes is solved. The problem of insufficient settlement stability and coating properties of the substances is achieved, which achieves excellent adhesion of the electrode composite material layer to the current collector and improves the performance of the lithium-ion battery.
Patent Information
- Application Number
- CN202380050526.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-07-18
- Publication Date
- 2025-02-18
AI Technical Summary
The conventional adhesive composition for lithium-ion battery electrodes has insufficient settling stability and coating properties, resulting in poor adhesion of the electrode composite material layer to the current collector.
The poly(meth)acrylamide copolymer containing (meth)acrylamide monomer and unsaturated carboxylic acid-based monomer is used as the binder composition, and the ratio of monomer components is adjusted to be between 30 and 80 mol The intrinsic viscosity of the polymer is controlled between % of (meth)acrylamide monomer and 20 to 70 mol% of unsaturated carboxylic acid group-containing monomer.
The settling stability and coating properties of the slurry composition for electrodes of lithium-ion batteries are significantly improved, and the adhesion of the electrode composite material layer to the current collector is enhanced, thereby improving the performance of the lithium-ion battery.
Smart Images

Figure BDA0005214308590000131 
Figure BDA0005214308590000181 
Figure BDA0005214308590000191
Abstract
Description
Technical Field
[0001] The invention relates to a binder composition for lithium ion battery electrodes. Background Art
[0002] In recent years, in order to achieve further high performance of lithium-ion batteries, the improvement of electrode materials has been actively studied. Generally, the electrode of a lithium-ion battery is formed by applying a slurry composition on a current collector and drying it, wherein the slurry composition contains a powdered electrode active material and a binder composition for dispersing the electrode active material in a solvent and bonding it to the current collector.
[0003] As such binder compositions, binder resins such as PVDF (polyvinylidene fluoride) and SBR (styrene-butadiene rubber) / CMC (carboxymethyl cellulose) have been widely used so far. However, as lithium-ion batteries become more advanced in performance, a binder having a stronger adhesive force than these binder resins is desired.
[0004] In addition, it is known that there is a kind of adhesive composition, it has a water-soluble polymer comprising (methyl) acrylamide monomer and acid-containing monomer, the containing ratio of the acid-containing monomer unit in the water-soluble polymer is more than 5 mass % and less than 70 mass %, and in the water-soluble polymer, the ratio of the water-soluble polymer with an inertial radius of less than 200nm is more than 95 mass % and less than 100 mass %. And, it is also recorded that by using such an adhesive composition, the low temperature characteristics of non-aqueous secondary batteries can be improved (for example, with reference to patent documentation 1).
[0005] Patent Document 1: International Publication No. 2017 / 163806 Summary of the invention
[0006] -Technical problem to be solved by the invention-
[0007] However, the binder composition described in Patent Document 1 has a problem in that the slurry composition containing the binder composition has insufficient sedimentation stability and also has a problem in that the slurry composition has poor coating properties because aggregation occurs in the slurry composition.
[0008] Therefore, the present invention is completed to solve the above-mentioned problems. Its purpose is to provide a binder composition for lithium ion battery electrodes, which can be used to obtain a slurry composition for lithium ion battery electrodes with excellent sedimentation stability and coating properties, and can also obtain a lithium ion battery electrode with excellent adhesion of the electrode composite material layer to the current collector.
[0009] -Technical solutions to solve technical problems-
[0010] In order to achieve the above-mentioned object, the binder composition for lithium ion battery electrodes of the present invention contains at least a polymer of a monomer component, namely a poly(meth)acrylamide copolymer, wherein the monomer component includes a (meth)acrylamide monomer and an unsaturated carboxylic acid group-containing monomer as monomer units, and the monomer component contains 30 to 80 mol % of the (meth)acrylamide monomer and 20 to 70 mol % of the unsaturated carboxylic acid group-containing monomer relative to its total amount of 100 mol %, and the inherent viscosity of the poly(meth)acrylamide copolymer is 3.5 to 7.5 dL / g.
[0011] - Effects of the Invention -
[0012] The binder composition for lithium ion battery electrodes of the present invention can provide a slurry composition for lithium ion battery electrodes having excellent sedimentation stability and coating properties, and can provide a lithium ion battery electrode having excellent adhesion of the electrode composite material layer to the current collector. DETAILED DESCRIPTION
[0013] Hereinafter, the binder composition for lithium ion battery electrodes of the present invention will be described.
[0014] The binder composition for lithium ion battery electrodes of the present invention contains at least a polymer of a monomer component, ie, a poly(meth)acrylamide copolymer, wherein the monomer component includes a (meth)acrylamide monomer and an unsaturated carboxylic acid group-containing monomer as monomer units.
[0015] <(Meth)acrylamide monomer>
[0016] The (meth)acrylamide monomer forming the (meth)acrylamide monomer unit is a monomer derived from a compound containing a (meth)acrylamide group, and examples of the (meth)acrylamide monomer include acrylamide and methacrylamide. It should be noted that the (meth)acrylamide monomer may be used alone or in combination of two or more.
[0017] The "(meth)acrylic acid" mentioned herein is defined as acrylic acid and / or methacrylic acid.
[0018] The content of the (meth)acrylamide monomer is 30 to 80 mol % based on 100 mol % of the total amount of the monomer components (ie, the (meth)acrylamide monomer, the unsaturated carboxylic acid group-containing monomer, and other polymerizable monomers described below).
[0019] This is because, in the case of less than 30 mol%, it is speculated that the hydrophilicity of the poly(methyl)acrylamide copolymer becomes high, and the dispersibility of the poly(methyl)acrylamide copolymer to the hydrophobic active material becomes insufficient, so there is a large amount of sedimentation in the slurry composition, and the sedimentation stability is reduced. In the case of more than 80 mol%, it is speculated that the expansion (volume increase) of the poly(methyl)acrylamide copolymer caused by the repulsion of the charge becomes insufficient, and it will not play a role as a steric hindrance, resulting in the aggregation of the active material, so a large amount of sedimentation occurs in the slurry composition, and the sedimentation stability is reduced, and the expansion of the poly(methyl)acrylamide copolymer caused by the repulsion of the charge becomes insufficient, and the substituent that can contribute to the bonding becomes less, so there is a situation where the adhesion (close adhesion strength) of the electrode composite material layer to the current collector is reduced.
[0020] The content of the (meth)acrylamide monomer unit is preferably 40 to 80 mol % relative to 100 mol % of the total amount of the monomer components, and more preferably 45 to 75 mol % from the viewpoint of improving the adhesion of the electrode composite material layer to the current collector.
[0021] <Unsaturated carboxylic acid group-containing monomer>
[0022] The unsaturated carboxylic acid group-containing monomer that forms the unsaturated carboxylic acid group-containing monomer unit is an anionic polymerizable monomer derived from an unsaturated carboxylic acid or its salt. Examples of monomers having an unsaturated carboxylic acid group include: monomers of α,β-unsaturated monocarboxylic acid system such as acrylic acid, methacrylic acid, crotonic acid; monomers of α,β-unsaturated dicarboxylic acid system such as maleic acid, fumaric acid, itaconic acid, citraconic acid. Examples of salts of unsaturated carboxylic acids include: sodium salts, potassium salts, lithium salts, ammonium salts, etc. of unsaturated carboxylic acids. It should be noted that the unsaturated carboxylic acid group-containing monomers can be used alone or in combination of two or more. As the unsaturated carboxylic acid group-containing monomer, preferably, monomers of α,β-unsaturated monocarboxylic acid system can be used, and more preferably, acrylic acid and methacrylic acid.
[0023] Relative to the total amount of monomer components 100 mol%, the content of unsaturated carboxylic acid group-containing monomer is 20-70 mol%. In the case of less than 20 mol%, it is speculated that the expansion of the poly (meth) acrylamide copolymer caused by the repulsion of the charge becomes insufficient, and it will not act as a steric hindrance, resulting in the aggregation of active materials, so a large amount of sedimentation occurs in the slurry composition, and the sedimentation stability is reduced, and the expansion of the poly (meth) acrylamide copolymer caused by the repulsion of the charge becomes insufficient, and the substituents that contribute to the adhesion become less, so there is a situation where the adhesion (close adhesion strength) of the electrode composite material layer to the current collector is reduced. In the case of more than 70 mol%, it is speculated that the hydrophilicity of the poly (meth) acrylamide copolymer becomes high, and the dispersibility of the hydrophobic active material becomes insufficient, so there is a large amount of sedimentation in the slurry composition, and the sedimentation stability is reduced.
[0024] It should be noted that the content of the unsaturated carboxylic acid group-containing monomer is preferably 20 to 60 mol % relative to 100 mol % of the total amount of monomer components, and more preferably 25 to 55 mol % from the viewpoint of improving the adhesion of the electrode composite material layer to the current collector.
[0025] In the present invention, in addition to the (meth)acrylamide monomer and the unsaturated carboxylic acid group-containing monomer, other polymerizable monomers may be contained as an optional component. Other polymerizable monomers include, for example, nonionic polymerizable monomers or crosslinkable monomers, anionic polymerizable monomers (excluding unsaturated carboxylic acid group-containing monomers), etc.
[0026] <Nonionic polymerizable monomer>
[0027] Examples of the nonionic polymerizable monomer include styrene, α-methylstyrene, (meth)acrylonitrile, alkyl (meth)acrylate, hydroxyalkyl (meth)acrylate, diacetone acrylamide, polyalkylene glycol (meth)acrylate, glycerol mono (meth)acrylate, vinyl pyrrolidone, vinyl oxazoline, vinyl acetate, acryloyl morpholine, etc. It should be noted that the nonionic polymerizable monomer may be used alone or in combination of two or more.
[0028] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, amyl (meth)acrylate, neopentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate (meth)acrylate monomers having a linear, branched or cyclic alkyl group having 1 to 30 carbon atoms, such as esters, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, 1-methyltridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate (stearoyl (meth)acrylate), isostearyl (meth)acrylate, eicosyl (meth)acrylate, docosyl (meth)acrylate, behenyl (meth)acrylate, tetracosyl (meth)acrylate, triacontyl (meth)acrylate, and cyclohexyl (meth)acrylate.
[0029] When a nonionic polymerizable monomer is contained, the content of the nonionic polymerizable monomer is preferably 1 to 40 mol %, more preferably 1 to 30 mol %, based on 100 mol % of the total amount of the monomer components.
[0030] <Crosslinkable monomer>
[0031] Examples of the crosslinkable monomer include amide group-containing crosslinkable monomers (e.g., methylenebis(meth)acrylamide, ethylenebis(meth)acrylamide, allyl(meth)acrylamide, hydroxyethylacrylamide, N-substituted acrylamide monomers (e.g., N,N-dimethylacrylamide, N,N-diethylacrylamide, N-hydroxymethylacrylamide, diacetoneacrylamide, isopropylacrylamide), triacrylformal, imido group-containing crosslinkable monomers (e.g., diacrylimide, etc.), nitrogen-free bifunctional crosslinking agents (e.g., divinylbenzene, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, allyl(meth)acrylate, etc.), and nitrogen-free polyfunctional crosslinking agents (e.g., pentaerythritol triacrylate, trimethylolpropane acrylate, tetraallyloxyethane, etc.). The crosslinkable monomers may be used alone or in combination of two or more.
[0032] When a crosslinkable monomer is contained, the content of the crosslinkable monomer is preferably 0.01 to 10 mol %, more preferably 0.01 to 5 mol %, and further preferably 0.01 to 2 mol %, based on 100 mol % of the total amount of the monomer components.
[0033] <Anionic polymerizable monomer>
[0034] Examples of the anionic polymerizable monomer include sulfonic acid monomers having a vinyl group, such as vinyl sulfonic acid, styrene sulfonic acid, 2-acrylamide-2-methylpropanesulfonic acid, etc. Salts such as sodium salts, potassium salts, lithium salts, and ammonium salts of sulfonic acid monomers having a vinyl group may also be used.
[0035] The anionic polymerizable monomer can be appropriately added within a range that does not impair the effects of the present invention.
[0036] In addition to the nonionic polymerizable monomers or crosslinkable monomers and anionic polymerizable monomers, cationic polymerizable monomers may be added within the scope of not destroying the effects of the present invention. Examples of cationic polymerizable monomers include tertiary amino polymerizable monomers and quaternary ammonium polymerizable monomers.
[0037] Examples of tertiary amino-based polymerizable monomers include polymerizable monomers (non-quaternary compounds) having a tertiary amino group, such as (meth)acrylate derivatives having a tertiary amino group and (meth)acrylamide derivatives having a tertiary amino group. Examples of (meth)acrylate derivatives having a tertiary amino group include dialkylaminoethyl (meth)acrylate (e.g., dimethylaminoethyl (meth)acrylate, etc.) and dialkylaminopropyl (meth)acrylate. Examples of (meth)acrylamide derivatives having a tertiary amino group include dialkylaminoalkyl (meth)acrylamide (e.g., dialkylaminopropyl (meth)acrylamide (e.g., dimethylaminopropyl acrylamide, etc.) and (meth)acrylamide-3-methylbutyldimethylamine.
[0038] The quaternary ammonium-based polymerizable monomer is a cationic copolymerizable monomer having a quaternary ammonium group and an ethylenic double bond, and examples thereof include: a quaternary compound of the tertiary amino-based polymerizable monomer, etc. The quaternary compound of the tertiary amino-based polymerizable monomer includes: a quaternary compound (quaternary ammonium salt) obtained by quaternizing the tertiary amino group of the tertiary amino-based polymerizable monomer with methyl chloride (methane chloride), methyl bromide, benzyl chloride (benzyl chloride), benzyl bromide, dimethylsulfuric acid, epichlorohydrin, etc.
[0039] <Method for producing poly(meth)acrylamide copolymer>
[0040] Next, an example of the method for producing the poly(meth)acrylamide copolymer of the present invention will be described in detail.
[0041] When manufacturing the poly(meth)acrylamide copolymer, the monomer components including the (meth)acrylamide monomer, the unsaturated carboxylic acid group-containing monomer and other monomers are copolymerized. In order to copolymerize these monomer components, for example, the monomer components, a polymerization initiator and a solvent are added to a prescribed reaction vessel to react. It should be noted that in this method, the monomer components can be added all at once or in batches. It is also possible to drip a part or all of the polymerization initiator into the reaction vessel while allowing the reaction to proceed.
[0042] As the polymerization initiator, for example, free radical polymerization initiators can be mentioned, and more specifically, peroxide compounds, sulfides, sulfenes, sulfinic acids, etc. can be mentioned, preferably peroxide compounds. It should be noted that peroxide compounds can also be used in combination with a reducing agent as a redox polymerization initiator. It should be noted that these polymerization initiators can be used alone or in combination of two or more.
[0043] Examples of the peroxide compound include organic peroxides and inorganic peroxides, and inorganic peroxides are preferred.
[0044] Examples of the organic peroxide include benzoyl peroxide, lauroyl peroxide, acetyl peroxide, octanoyl peroxide, 2,4-dichlorobenzoyl peroxide, isobutyl peroxide, acetylcyclohexylsulfonyl peroxide, t-butyl peroxypivalate, t-butylperoxy-2-ethylhexanoate, 1,1-di-t-butylperoxycyclohexane, 1,1-di-t-butylperoxy-3,3,5-trimethylcyclohexane, 1,1-di-t-hexylperoxy-3,3,5-trimethylcyclohexane, isopropyl peroxydicarbonate, isobutyl peroxydicarbonate, s-butyl peroxydicarbonate, n-butyl peroxydicarbonate, 2-ethylhexyl peroxydicarbonate, diisopropyl ... (4-t-butylcyclohexyl) peroxydicarbonate, t-amyl peroxy-2-hexanoic acid ethyl ester, 1,1,3,3-tetramethylbutyl peroxy-hexanoic acid ethyl ester, 1,1,2-trimethylpropyl peroxy-2-hexanoic acid ethyl ester, t-butyl peroxyisopropyl monocarbonate, t-amyl peroxyisopropyl monocarbonate, t-butyl peroxy-2-ethylhexyl carbonate, t-butyl peroxyallyl carbonate, t-butyl peroxyisopropyl carbonate, 1,1,3,3-tetramethylbutyl peroxyisopropyl monocarbonate, 1,1,2-trimethylpropyl peroxyisopropyl monocarbonate, 1,1,3,3-tetramethylbutyl peroxyisophthalate peroxy isononate), 1,1,2-trimethylpropyl peroxy isononate, t-butyl peroxybenzoate, etc.
[0045] Examples of the inorganic peroxide include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate; bromates such as hydrogen peroxide, potassium permanganate, sodium bromate, and potassium bromate; perborates such as sodium perborate, potassium perborate, and ammonium perborate; percarbonates such as sodium percarbonate, potassium percarbonate, and ammonium percarbonate; and superphosphates such as sodium superphosphate, potassium superphosphate, and ammonium superphosphate.
[0046] As the polymerization initiator, an azo compound can also be used. Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionamidine) and salts thereof.
[0047] As the polymerization initiator, preferably, an inorganic peroxide is used, more preferably, a persulfate is used, and further preferably, ammonium persulfate is used.
[0048] The addition ratio of the polymerization initiator is, for example, preferably 0.01 to 10 parts by mass, and more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the total amount of the monomer components.
[0049] As the solvent, water, ketone solvents (for example, acetone, methyl ethyl ketone), monohydric alcohol solvents (for example, methanol, ethanol, propanol, isopropanol, butanol), glycol ether solvents (for example, ethylene glycol monoethyl ether, propylene glycol monomethyl ether), solvents that can be mixed with water (for example, ester-ether solvents such as propylene glycol monomethyl ether acetate), and water is preferably mentioned. It should be noted that when tap water is used as a solvent, a chelating agent (ethylenediaminetetraacetic acid, etc.) can also be added in a prescribed ratio to remove the metal. It should be noted that these solvents can be used alone or in combination of two or more. The addition ratio of the solvent is not particularly limited and can be appropriately set according to the purpose and use.
[0050] In this method, a chain transfer agent may be appropriately added together with the monomer components, the polymerization initiator and the solvent.
[0051] Examples of chain transfer agents include (meth)allyl compounds such as (meth)allyl sulfonates, mercaptoethanol, thioglycolic acid, mercaptopropionic acid, thiosalicylic acid, thiolactic acid, aminoethanethiol, thioglycerol, thiomalic acid, and isopropyl alcohol, etc. It should be noted that these chain transfer agents may be used alone or in combination of two or more.
[0052] As used herein, "(meth)allyl" is defined as allyl and / or methallyl.
[0053] Examples of the (meth)allyl sulfonate include sodium allyl sulfonate, sodium methallyl sulfonate, potassium allyl sulfonate, and potassium methallyl sulfonate.
[0054] When a chain transfer agent is added, the addition ratio of the chain transfer agent is preferably 0.001 to 0.4 parts by mass, more preferably 0.008 to 0.36 parts by mass, and even more preferably 0.008 to 0.27 parts by mass, relative to the total amount (100 parts by mass) of the monomer components.
[0055] The polymerization conditions for producing the poly(meth)acrylamide copolymer vary depending on the types of monomer components, polymerization initiators, solvents, etc. The polymerization temperature is, for example, preferably 30° C. to 100° C., more preferably 50° C. to 95° C.
[0056] The polymerization time is preferably 0.5 hours to 24 hours, more preferably 1 hour to 12 hours. It should be noted that the polymerization reaction can be terminated by adding a known polymerization terminator (e.g., sodium pyrosulfite, sodium thiosulfate, sodium sulfite, 4-methoxyphenol, thiourea, etc.) as required.
[0057] The pH of the reaction solution during polymerization is, for example, preferably 1 to 6, more preferably 1.5 to 5. The pH can be adjusted by adding known acids such as hydrochloric acid, sulfuric acid, and phosphoric acid, or known bases such as sodium hydroxide, potassium hydroxide, and lithium hydroxide.
[0058] The pH value of the reaction solution containing the poly(meth)acrylamide copolymer and water (that is, the binder composition for lithium ion battery electrodes) can be adjusted by treating the poly(meth)acrylamide copolymer obtained by polymerization with a neutralizing agent. As the neutralizing agent, for example, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, and ammonia or organic amines can be cited. The adjusted pH value is preferably 2 to 11, and more preferably 6 to 8.
[0059] By such a reaction, a polymer of monomer components, namely a poly(meth)acrylamide copolymer, is obtained. The monomer components include (meth)acrylamide monomer and unsaturated carboxylic acid group-containing monomer as monomer units, thereby obtaining a binder composition for lithium ion battery electrodes containing the poly(meth)acrylamide copolymer.
[0060] The intrinsic viscosity of the poly(meth)acrylamide copolymer is 3.5 to 7.5 dL / g. This is because, when it is less than 3.5 dL / g, the adhesion (adhesion strength) of the electrode composite material layer to the current collector is reduced. When it is greater than 7.5 dL / g, in the slurry composition, the cohesion of the poly(meth)acrylamide copolymer relative to the conductive aid is improved, and thus the coating property of the slurry composition is reduced.
[0061] That is, in the binder composition for lithium ion battery electrodes of the present invention, the inherent viscosity of the poly(methyl)acrylamide copolymer is 3.5 to 7.5 dL / g, so that a slurry composition for lithium ion battery electrodes having excellent coating properties can be provided, and a lithium ion battery electrode having excellent adhesion of the electrode composite material layer to the current collector can be provided.
[0062] From the viewpoint of improving the adhesion of the electrode material layer to the current collector and the coating properties of the slurry composition, the intrinsic viscosity of the poly(meth)acrylamide copolymer is preferably 4.2 dL / g or more and 6.5 dL / g or less.
[0063] The "intrinsic viscosity" mentioned here is a characteristic value indicating the molecular weight of a polymer or the extension of a molecular chain in a solution, meaning the volume per unit weight occupied by the polymer in a solution, and can be calculated by gel permeation chromatography (GPC) as described in the examples below.
[0064] The weight average molecular weight (Mw) of the poly(meth)acrylamide copolymer is preferably more than 2 million and less than 4 million. This is because it is speculated that when the weight average molecular weight is less than 2 million, the molecular size of the poly(meth)acrylamide copolymer is insufficient and cannot function as a steric hindrance, resulting in agglomeration of the active material, and therefore there is a large amount of sedimentation in the slurry composition, and the sedimentation stability is reduced. In the case where the weight average molecular weight is greater than 4 million, there is a situation where the adhesion of the electrode composite material layer to the current collector is reduced.
[0065] The weight average molecular weight of the poly(meth)acrylamide copolymer can be appropriately adjusted, for example, by the types and amounts of the (meth)acrylamide monomer, the unsaturated carboxylic acid group-containing monomer, and other polymerizable monomers as the polymerization components.
[0066] The “weight average molecular weight” referred to herein refers to a weight average molecular weight obtained by gel permeation chromatography (GPC) measurement, and can be determined by the method described in Examples described later.
[0067] Preferably, in the binder composition for lithium ion battery electrodes of the present invention, when the intrinsic viscosity of the poly(meth)acrylamide copolymer is X [dL / g] and the weight average molecular weight of the poly(meth)acrylamide copolymer is Y [million], the relationship of the following formula (1) holds.
[0068] [Formula 1]
[0069] 1.35≤X / Y≤2.05 (1)
[0070] This is because, when X / Y is 1.35 or more, the adhesion (adhesion strength) of the electrode composite material layer to the current collector is further improved, and when X / Y is 2.05 or less, the coating properties of the slurry composition are further improved.
[0071] The adhesive composition containing the poly(meth)acrylamide copolymer may contain additives such as a dispersant, a leveling agent, an antioxidant, a tackifier, an antiseptic (eg, a slime control agent), a rust preventive, and a defoaming agent as required.
[0072] When these additives are added, the content of the additives is preferably 5% by mass or less based on 100% by mass of the total amount of the pressure-sensitive adhesive composition.
[0073] <Slurry composition for lithium-ion battery electrodes>
[0074] The slurry composition for lithium ion battery electrodes of the present invention contains at least the above-mentioned binder composition for lithium ion battery electrodes and an electrode active material.
[0075] The electrode active material is not particularly limited as long as it is a material that can reversibly embed and deintercalate lithium ions by applying a potential in an electrolyte. Examples of the electrode active material include negative electrode active materials and positive electrode active materials. It should be noted that these electrode active materials can be used alone or in combination of two or more.
[0076] Examples of the negative electrode active material include carbon materials such as graphite, coke, acetylene black, and mesophase microcarbon beads; lithium metal, lithium alloys such as lithium-silicon, and lithium-tin; lithium titanate, silicon, and silicon oxide.
[0077] Examples of the positive electrode active material include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides of transition metals such as Fe, Co, Ni, and Mn and lithium, and transition metal sulfides.
[0078] The content of the binder composition for lithium ion battery electrodes is preferably 0.5 to 10% by mass, more preferably 0.8 to 5% by mass, based on 100% by mass of the total solid content of the slurry composition for lithium ion battery electrodes.
[0079] The slurry composition for lithium ion battery electrodes of the present invention may contain, in addition to the above-mentioned binder composition for lithium ion battery electrodes and the electrode active material, other known components such as a conductive aid or a dispersant for a conductive aid, a viscosity adjusting solvent, a coating property adjusting solvent, a thickener, a pH adjuster, and an anticorrosive agent.
[0080] In addition, when these other components are added, the content of the other components is preferably 5% by mass or less based on 100% by mass of the total amount of the slurry composition for lithium ion battery electrodes.
[0081] Examples of the conductive additive include carbon black such as acetylene black and Ketjen black, conductive carbon such as vapor-grown carbon fiber and carbon nanotube, and fine powders of Cu, Ni, Al, Si or alloys thereof having an average particle size of 10 μm or less.
[0082] When adding a conductive aid, the content of the conductive aid is preferably 0 to 5% by mass, more preferably 0.5 to 2% by mass, based on 100% by mass of the total solid content of the slurry composition for lithium ion battery electrodes.
[0083] The slurry composition for lithium ion battery electrodes of the present invention may contain a binder composition other than the binder composition for lithium ion battery electrodes containing the poly(meth)acrylamide copolymer. However, the content of the poly(meth)acrylamide copolymer in the entire binder is preferably 50% by mass or more.
[0084] As other adhesive compositions, for example, there can be mentioned adhesive compositions containing fluorine-based resins (polyvinylidene fluoride, polytetrafluoroethylene, etc.), polyolefins (polyethylene, polypropylene, etc.), polymers having unsaturated bonds (styrene-butadiene rubber, isoprene rubber, butadiene rubber, etc.), carboxymethyl cellulose salts, polyvinyl alcohol copolymers, polyvinyl pyrrolidone, etc. It should be noted that these adhesive compositions may be used alone or in combination of two or more.
[0085] <Method for producing slurry composition for lithium ion battery electrodes>
[0086] Examples of a method for producing the slurry composition for lithium ion battery electrodes include a method in which the binder composition for lithium ion battery electrodes, an electrode active material, a conductive auxiliary agent, and the like are placed in a container and mixed.
[0087] In addition, the mixing device of the slurry composition is not particularly limited, and examples thereof include a rotation-revolution mixer, a ball mill, a sand mill, a homogenizer, a planetary mixer, and a Hobart mixer.
[0088] <Electrodes for lithium-ion batteries>
[0089] The lithium ion battery electrode of the present invention is obtained by applying the slurry composition for lithium ion battery electrodes on a current collector and drying the slurry composition for lithium ion battery electrodes, and has an electrode composite material layer formed of the slurry composition for lithium ion battery electrodes on the current collector.
[0090] The current collector is not particularly limited, and examples thereof include: metal materials such as copper, iron, aluminum, nickel, titanium, gold, tantalum, platinum, stainless steel, and nickel-plated steel; and carbon materials such as carbon cloth and carbon paper. It should be noted that as the negative electrode current collector, a current collector formed of copper is preferably used, and as the positive electrode current collector, a current collector formed of aluminum is preferably used.
[0091] The electrode composite material layer can be formed, for example, by coating the prepared lithium battery electrode slurry composition on both sides or one side of the current collector, and then drying it at a specified temperature (e.g., 80° C.) for a specified time (e.g., 60 minutes). It should be noted that from the perspective of obtaining an electrode composite material layer having a desired density, it is preferred to use a roller press or the like for pressurization treatment.
[0092] The thickness of the electrode material layer is not particularly limited, but is preferably 5 to 300 μm, more preferably 10 to 250 μm. By setting the thickness within this range, sufficient lithium ion insertion / release function for a high-density current value can be easily obtained.
[0093] The form of the current collector is not particularly limited. In the case of metal materials, metal foils, metal cylinders, metal coils, metal plates, etc. can be used; in the case of carbon materials, carbon plates, carbon films, carbon cylinders, etc. can be used.
[0094] Examples of the coating method include a coating method using a coating apparatus such as a comma coater, a gravure coater, a micro gravure coater, a die coater, a bar coater, or an applicator.
[0095] The temperature during drying is preferably 60 to 200° C., and more preferably 75 to 195° C. The atmosphere during drying may be dry air or an inert atmosphere.
[0096] <Lithium-ion battery>
[0097] The lithium ion battery of the present invention includes the above-mentioned lithium ion battery electrodes (positive electrode and negative electrode), a separator, and an electrolyte.
[0098] The separator is not particularly limited as long as it can electrically insulate the positive electrode from the negative electrode and can retain the electrolyte. For example, it can be a single-layer or multi-layer porous film, non-woven fabric, etc. formed of polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate, polyamide, polyetherimide, etc.
[0099] The electrolyte solution can include: a non-aqueous electrolyte solution in which a supporting electrolyte is dissolved in a non-aqueous solvent, etc. As the non-aqueous solvent, for example, chain carbonate solvents such as diethyl carbonate, dimethyl carbonate, and methyl ethyl carbonate; cyclic carbonate solvents such as ethylene carbonate, propylene carbonate, and butylene carbonate; chain ether solvents such as 1,2-dimethoxyethane; cyclic ether solvents such as tetrahydrofuran, 2-methyltetrahydrofuran, sulfolane, and 1,3-dioxolane; chain ester solvents such as methyl formate, methyl acetate, and methyl propionate; cyclic ester solvents such as γ-butyrolactone and γ-valerolactone; and acetonitrile, etc. It should be noted that the electrolyte solution can be used alone or in combination of two or more, but preferably a combination of a mixed solvent containing a cyclic carbonate and a chain carbonate.
[0100] The supporting electrolyte uses a lithium salt. As a lithium salt, for example, it can be cited: LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. Among them, LiPF6, LiClO4, and CF3SO3Li, which are easily soluble in solvents and show a high degree of dissociation, are preferably used. The higher the degree of dissociation of the supporting electrolyte used, the higher the lithium ion conductivity, so the lithium ion conductivity can be adjusted according to the type of supporting electrolyte. It should be noted that these supporting electrolytes can be used alone or in combination of two or more.
[0101] The form of the lithium-ion battery is not particularly limited, and examples thereof include: a cylindrical type in which sheet electrodes and separators are formed into a spiral shape, a cylindrical type with an inside-out structure formed by combining granular electrodes and separators, a coin type in which granular electrodes and separators are stacked, etc. By housing the battery in the above form in any housing, it can be made into any shape such as a coin type, a cylindrical type, a square type, etc. and used.
[0102] There is no particular limitation on the manufacturing method of lithium-ion batteries, as long as they are assembled in appropriate steps according to the structure of the battery. For example, a negative electrode is placed on a casing, an electrolyte and a separator are provided thereon, and a positive electrode is placed opposite to the negative electrode, and fixed by a gasket and a sealing plate, thereby manufacturing a lithium-ion battery.
[0103] -Example-
[0104] The present invention is described below with reference to the following embodiments. It should be noted that the present invention is not limited to the following embodiments, and various modifications and changes can be made based on the main idea of the present invention and on the basis of the following embodiments, which all fall within the protection scope of the present invention.
[0105] (Example 1)
[0106] <Preparation of binder composition for lithium-ion battery electrodes>
[0107] As part of the polymer components, 85 mol % of the total amount of the polymer components (acrylamide, acrylic acid, N,N-dimethylacrylamide) listed in Table 1 (including sodium methallyl sulfonate shown in Table 1) was prepared and diluted with distilled water to a polymer component concentration of 14 mass %.
[0108] Next, the obtained solution was placed in a 500 mL separable flask, and then, while blowing nitrogen into the solution, ammonium persulfate (APS) as a polymerization initiator was added at 50° C. to polymerize. Then, the temperature reached 70° C. by heating accompanying the polymerization, and this temperature was maintained, and after 90 minutes had passed since the addition of the ammonium persulfate, the remaining portion (15 mol%) of the polymerization component and additional ammonium persulfate were added.
[0109] Next, the temperature was raised to 75 to 80° C. and the reaction was continued for 120 minutes while maintaining the temperature. Then, sodium pyrosulfite (Na 2 S 2 O 5 ) as a polymerization terminator (reducing agent) and dilution water were added, followed by cooling.
[0110] Then, after cooling to 40° C., sodium hydroxide was added as a neutralizing base in an amount equimolar to that of acrylic acid to obtain a binder composition for lithium ion battery electrodes containing a polyacrylamide copolymer and water.
[0111] <Calculation of weight average molecular weight and intrinsic viscosity>
[0112] Next, the weight average molecular weight (Mw) of the polyacrylamide copolymer in the obtained adhesive composition was calculated. More specifically, 0.1 g of the adhesive composition obtained in this example was dissolved in 5.0 g of a phosphate buffer solution having a pH value of 7, and the concentration of the non-volatile component (solid content) contained in the adhesive composition in the solution was adjusted to 1.0 g / L, and the weight average molecular weight (Mw) of the sample was calculated from the chromatogram (chart) obtained by gel permeation chromatography (GPC). The above results are shown in Table 1.
[0113] The above solution was used to calculate the intrinsic viscosity of the polyacrylamide copolymer in the obtained adhesive composition using a viscosity detector in a gel permeation chromatography (GPC) device. The above results are shown in Table 1.
[0114] It should be noted that the viscosity detector measures the relative viscosity of the polymer solution relative to the viscosity of the solvent. The relative viscosity is expressed as the specific viscosity η sp Indicates that the specific viscosity η sp The viscosity of the solution is η, the viscosity of the solvent is η s The rate of increase in viscosity at this time is defined by the following formula (2).
[0115] [Formula 2]
[0116] η sp =(η-η s ) / η s (2)
[0117] The increase in viscosity per unit concentration c of the polymer is calculated as the reduced viscosity ηred It is represented by the following formula (3).
[0118] [Formula 3]
[0119] η red =η sp / c (3)
[0120] In the following formula (4), the reduced viscosity η is calculated by setting the unit concentration c of the polymer to zero. red The intrinsic viscosity can be experimentally calculated by extrapolation (that is, the value when the unit concentration c is made as close to 0 as possible in the following formula (4) is taken as the intrinsic viscosity).
[0121] [Formula 4]
[0122]
[0123] The measuring device and measuring conditions used for calculation of the weight average molecular weight and the intrinsic viscosity are as follows.
[0124] Device: Model OMNISEC RESOLVE&REVEAL (Malvern)
[0125] Chromatography column: Model TSKgel GMPW XL (Tosoh Corporation)
[0126] Mobile phase: phosphate buffer
[0127] Column flow rate: 0.8mL / min
[0128] Sample concentration: 1.0g / L
[0129] Injection volume: 100 μL
[0130] <Preparation of slurry composition for lithium-ion battery electrodes>
[0131] 96 parts by mass of graphite (manufactured by Shanghai Shanshan New Material Co., Ltd., trade name: FSNC-1) as an active material, 1 part by mass of carbon black (manufactured by IMERYS Graphite & Carbon Belgium, trade name: Super P Li) as a conductive aid, and 3 parts by mass of the prepared binder composition (converted to solid content) were placed in a container, diluted with distilled water to a solid content concentration of 5 to 10 Pa·s (measured by a rheometer) of the viscosity of the slurry composition, and kneaded with a rotation-revolution mixer (rotation speed: 500 rpm, revolution speed: 1500 rpm, time: 5 minutes) to obtain a slurry composition for lithium ion battery electrodes.
[0132] <Evaluation of slurry sedimentation stability>
[0133] The prepared slurry composition (about 20 g) was placed in a container and allowed to stand, and the sedimentation stability of the slurry was evaluated 3 days and 7 days after the preparation date according to the following evaluation criteria in a tactile evaluation using a glass rod (diameter: 3 mm).
[0134] No slurry settling was observed: ◎
[0135] The slurry had some settling but could be redispersed by stirring with a glass rod for one minute: o
[0136] A large amount of slurry settles, and the sediment is strongly agglomerated at the bottom of the container. It cannot be stirred with a glass rod and cannot be redispersed: ×
[0137] <Manufacturing of electrodes (negative electrodes) for lithium-ion batteries>
[0138] The prepared lithium ion battery electrode slurry composition was applied onto a copper foil (thickness: 18 μm) as a current collector using an automatic coating device (Tester Sangyo Co., Ltd., trade name: PI-1210) to a coating amount of 10 mg / cm 2 The electrode composite material layer was formed by drying in a dryer at 80°C for 60 minutes. Then, the electrode composite material layer was pressed by a roller press to a density of 1.5 g / cm 3 , thus obtaining an electrode for a lithium ion battery.
[0139] It should be noted that the ratio of the binder in the electrode composite material layer was 3% by mass.
[0140] <Evaluation of slurry coating properties>
[0141] The slurry composition was applied to a current collector and dried to form an electrode composite material layer (before punching), and the surface of the electrode composite material layer was visually observed to evaluate coating properties according to the following evaluation criteria.
[0142] No agglomerates or uneven coating were observed on the surface of the electrode composite material layer: ◎
[0143] Some aggregates were observed on the surface of the electrode composite material layer, and the coating was uneven: ○
[0144] A large amount of agglomerates were observed on the surface of the electrode composite material layer, and the coating was uneven: ×
[0145] <Evaluation of interfacial peel strength of electrodes>
[0146] First, a sample with a width of 2.5 cm and a length of 5.5 cm was cut out from the above-mentioned electrode (negative electrode) for lithium-ion batteries, and the active material surface of the sample was bonded to an aluminum plate with a double-sided tape (made by Nitto Denko Corporation, No. 510) to make a test piece. Then, under the condition of 25°C, a tensile compression universal testing machine (made by INTESCO Corporation, trade name: Model 205) was used to measure the stress when the current collector (copper foil) was peeled off from one end of the test piece in a 180° direction at a speed of 300 mm / min. It should be noted that the measurement was carried out twice, and the average value was calculated as the interfacial peeling strength of the electrode. The greater the interfacial peeling strength, the higher the adhesion strength between the current collector and the electrode composite material layer, and the more difficult it is for the electrode active material to be peeled off from the current collector.
[0147] As a reference sample, an electrode formed by replacing the binder composition of Example 1 with the following slurry composition was prepared, in which 1.5 parts by mass of SBR (styrene-butadiene rubber, manufactured by JSR Corporation, trade name: TRD104A) and 1.5 parts by mass of CMC (carboxymethyl cellulose, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., trade name: BSH-6) were used in terms of solid content. The interfacial peeling strength of the electrode was calculated by the same method, and the ratio of the interfacial peeling strength of this example to the interfacial peeling strength of the reference sample was calculated. The interfacial peeling strength was evaluated according to the following evaluation criteria. The above results are shown in Table 1.
[0148] The interfacial peel strength is more than twice that of the reference sample: A
[0149] The interfacial peel strength is 1.2 times greater than that of the reference sample: B
[0150] The interfacial peel strength is more than 1 times and less than 1.2 times the interfacial peel strength of the reference sample: C
[0151] The interfacial peel strength is less than 1 times the interfacial peel strength of the reference sample: D
[0152] (Examples 2 to 14, Comparative Examples 1 to 5)
[0153] A binder composition for lithium ion battery electrodes, a slurry composition for lithium ion battery electrodes, and an electrode (negative electrode) for lithium ion battery were prepared in the same manner as in Example 1 except that the type and addition amount of the polymerized component were changed to the conditions shown in Table 1.
[0154] Then, calculation of weight average molecular weight, calculation of intrinsic viscosity, evaluation of sedimentation stability of slurry, evaluation of coating properties of slurry, and evaluation of interfacial peel strength of electrode were performed in the same manner as in Example 1. The above results are shown in Tables 1 to 3.
[0155] (Example 15)
[0156] First, in the same manner as in Example 1, a binder composition for lithium ion battery electrodes was prepared.
[0157] Next, 96 parts by mass of graphite (manufactured by Shanghai Shanshan New Material Co., Ltd., trade name: FSNC-1) as an active material, 1 part by mass of carbon black (manufactured by IMERYS Graphite & Carbon Belgium, trade name: Super P Li) as a conductive aid, 2.1 parts by mass of the prepared binder composition (converted as solid content), and 0.9 parts by mass of SBR (styrene-butadiene rubber, manufactured by JSR Corporation [JSR Corporation], trade name: TRD104A) as another binder composition (converted as solid content) were placed in a container, diluted with distilled water to a solid content concentration of 5 to 10 Pa·s (measured by a rheometer) of the slurry composition, and kneaded with a rotation-revolution mixer (rotation speed: 500 rpm, revolution speed: 1500 rpm, time: 5 minutes) to obtain a slurry composition for lithium ion battery electrodes.
[0158] It should be noted that in the slurry composition for lithium ion battery electrodes, the mass ratio of the prepared binder composition (solid content) to SBR (styrene-butadiene rubber, solid content) as another binder composition is, the prepared binder composition: SBR (styrene-butadiene rubber) as another binder composition = 70:30.
[0159] Then, in the same manner as in Example 1, a lithium ion battery electrode (negative electrode) was prepared, and the weight average molecular weight, intrinsic viscosity, sedimentation stability of the slurry, coating properties of the slurry, and interfacial peeling strength of the electrode were calculated. The above results are shown in Table 2.
[0160] (Example 16)
[0161] First, in the same manner as in Example 4 above, a binder composition for lithium ion battery electrodes was prepared.
[0162] Next, 67.2 parts by mass of graphite (manufactured by Shanghai Shanshan New Material Co., Ltd., trade name: FSNC-1) as an active material, 28.8 parts by mass of silicon oxide (SiO) as an active material (manufactured by OSAKA Titanium Technologies, trade name: SiO (CC powder) for negative electrode material), 1 part by mass of carbon black (manufactured by IMERYS Graphite & Carbon Belgium, trade name: Super P Li) as a conductive aid, and 3 parts by mass of the prepared binder composition (in terms of solid content) were placed in a container, diluted with distilled water to a solid content concentration of 5 to 10 Pa·s (measured by a rheometer) of the slurry composition, and kneaded with a rotation-revolution mixer (rotation speed: 500 rpm, revolution speed: 1500 rpm, time: 5 minutes) to obtain a slurry composition for lithium ion battery electrodes.
[0163] It should be noted that the mass ratio of graphite to silicon oxide in the slurry composition for lithium ion battery electrodes was graphite:silicon oxide=70:30.
[0164] Then, in the same manner as in Example 1, a lithium ion battery electrode (negative electrode) was prepared, and the weight average molecular weight, intrinsic viscosity, sedimentation stability of the slurry, coating properties of the slurry, and interfacial peeling strength of the electrode were calculated. The above results are shown in Table 2.
[0165] (Examples 17-18)
[0166] First, in the same manner as in Example 4 above, a binder composition for lithium ion battery electrodes was prepared.
[0167] Next, a slurry composition for lithium ion battery electrodes was prepared in the same manner as in Example 16 except that the mass ratio of graphite to silicon oxide (graphite:silicon oxide) in the slurry composition for lithium ion battery electrodes was changed to the ratio shown in Table 2.
[0168] Then, in the same manner as in Example 1, a lithium ion battery electrode (negative electrode) was prepared, and the weight average molecular weight, intrinsic viscosity, sedimentation stability of the slurry, coating properties of the slurry, and interfacial peeling strength of the electrode were calculated. The above results are shown in Table 2.
[0169] (Example 19)
[0170] First, a binder composition for lithium ion battery electrodes was prepared in the same manner as in Example 4. A trace amount (1000 ppm) of a viscosity control agent (manufactured by THOR JAPAN, trade name: ACTICIDE LA5008) was added to the prepared binder composition for lithium ion battery electrodes as an additive.
[0171] Then, similarly to Example 1, a lithium ion battery electrode slurry composition and a lithium ion battery electrode (negative electrode) were prepared, and the weight average molecular weight was calculated, the intrinsic viscosity was calculated, the sedimentation stability of the slurry was evaluated, the coating property of the slurry was evaluated, and the interface peeling strength of the electrode was evaluated. The above results are shown in Table 2.
[0172] (Comparative Example 6)
[0173] The type and addition amount of the polymerization components were changed to the conditions shown in Table 3, and after obtaining the copolymer by the adjustment method based on Example 14 of WO2017 / 163806, a binder composition was prepared using sodium hydroxide as a neutralizing agent. In addition, a slurry composition for lithium ion battery electrodes and an electrode (negative electrode) for lithium ion batteries were prepared in the same manner as in Example 1 above.
[0174] Then, the weight average molecular weight was calculated, the intrinsic viscosity was calculated, the sedimentation stability of the slurry was evaluated, the coating property of the slurry was evaluated, and the interfacial peeling strength of the electrode was evaluated in the same manner as in Example 1. The above results are shown in Table 3.
[0175]
Table 1
[0176]
[0177]
Table 2
[0178]
[0179]
Table 3
[0180]
[0181] As shown in Tables 1 to 2, it can be seen that the lithium ion battery electrode binder composition of Examples 1 to 19, which contains 30 to 80 mol % of acrylamide and 20 to 70 mol % of acrylic acid relative to 100 mol % of the total amount of monomer components (acrylamide, acrylic acid and other polymerizable monomers), and the inherent viscosity of the polyacrylamide copolymer is 3.5 to 7.5 dL / g, can provide a slurry composition for lithium ion battery electrodes with excellent sedimentation stability and coating properties, and can provide a lithium ion battery electrode with excellent adhesion of the electrode composite material layer to the current collector.
[0182] On the other hand, as shown in Table 3, it can be seen that in Comparative Example 1 in which the content of acrylamide is greater than 80 mol% (i.e., 89 mol%) and the content of acrylic acid is less than 20 mol% (i.e., 10 mol%) relative to 100 mol% of the total amount of monomer components, a large amount of sedimentation occurs in the slurry, there is a lack of sedimentation stability, the interfacial peeling strength of the electrode is small, and the adhesion (close bonding strength) of the electrode composite material layer to the current collector is lacking.
[0183] It can also be seen that in Comparative Examples 2 and 3 in which the content of acrylamide relative to 100 mol% of the total amount of monomer components is less than 30 mol% (i.e., 15 to 20 mol%) and the content of acrylic acid is greater than 70 mol% (i.e., 79 to 84 mol%), a large amount of sedimentation occurs in the slurry and the sedimentation stability is lacking.
[0184] It is also found that in Comparative Example 4 in which the intrinsic viscosity of the polyacrylamide copolymer was greater than 7.5 dL / g (ie, 8.3 dL / g), the coating properties of the slurry composition for lithium ion battery electrodes were poor.
[0185] It is also known that in Comparative Example 5 where the intrinsic viscosity of the polyacrylamide copolymer is less than 3.5 dL / g (ie, 2.9 dL / g), the interfacial peeling strength of the electrode is small and the adhesion (adhesion strength) of the electrode composite material layer to the current collector is poor.
[0186] Finally, it was found that in Comparative Example 6 in which the intrinsic viscosity of the polyacrylamide copolymer was greater than 7.5 dL / g (ie, 9.2 dL / g), the coating property of the slurry composition for lithium ion battery electrodes was poor.
[0187] - Industrial Applicability -
[0188] In summary, the present invention is applicable to a binder composition for lithium ion battery electrodes used in a slurry composition for lithium ion battery electrodes.
Claims
1. A binder composition for lithium ion battery electrodes, comprising at least a polymer of a monomer component, namely a poly(meth)acrylamide copolymer, wherein the monomer component comprises a (meth)acrylamide monomer and an unsaturated carboxylic acid group-containing monomer as monomer units, characterized in that: The monomer component contains 30 to 80 mol % of the (meth)acrylamide monomer and 20 to 70 mol % of the unsaturated carboxylic acid group-containing monomer relative to 100 mol % of the total amount thereof. The intrinsic viscosity of the poly(meth)acrylamide copolymer is 3.5 to 7.5 dL / g.
2. The binder composition for lithium ion battery electrodes according to claim 1, characterized in that: The weight average molecular weight of the poly(meth)acrylamide copolymer is 2 million or more and 4 million or less.
3. The binder composition for lithium ion battery electrodes according to claim 1, characterized in that: When the intrinsic viscosity of the poly(meth)acrylamide copolymer is X [dL / g] and the weight average molecular weight of the poly(meth)acrylamide copolymer is Y [million], the following relationship (1) holds: [Formula 1] 1.35≤X / Y≤2.05 (1).
4. The binder composition for lithium ion battery electrodes according to claim 1, characterized in that: The monomer component contains 45 to 75 mol % of the (meth)acrylamide monomer and 25 to 55 mol % of the unsaturated carboxylic acid group-containing monomer, based on 100 mol % of the total amount thereof.
5. A slurry composition for lithium ion battery electrodes, characterized in that: The lithium ion battery electrode binder composition comprises the binder composition for lithium ion battery electrodes according to any one of claims 1 to 4 and an electrode active material.
6. A lithium ion battery electrode, characterized in that: The invention has an electrode composite material layer on a current collector, wherein the electrode composite material layer is formed from the slurry composition for lithium ion battery electrodes according to claim 5 .
7. A lithium ion battery, characterized in that: It comprises the electrode for lithium ion battery according to claim 6.
Citation Information
Patent Citations
Binder composition for nonaqueous secondary battery electrodes, slurry composition for nonaqueous secondary battery electrodes, electrode for nonaqueous secondary batteries, and nonaqueous secondary battery
WO2017163806A1
Cited By
Binder, negative electrode slurry, negative electrode plate and battery
CN120442187A